Study of the effect on flow rate for planar type polymer-based diaphragm piezoelectric actuated valveless micropump for insulin delivery. Issue 1 (2nd January 2016) - Revathi, S.; Padmanabhan, R.
Abstract: Micro-electromechanical systems are electrically sensed and actuated mechanical devices that are in micrometre-sized overall dimensions. The microsize of the system enables it to be used in several critical applications including healthcare where the system performance can be precisely controlled. One such application is micropump for drug delivery. Micropumps can be either valve based or valveless. Valve-based micropumps have mechanical check valves to control and deliver drugs through flaps or membranes. In valveless micropumps, the control is made through a diffuser/nozzle arrangement which regulates the liquid flow rate. In this paper, a valveless insulin pump based on piezoelectric actuation made of polymer-based material as diaphragm in planar type is constructed and the dependency of flow rate with material properties and size is studied. The modelling of the pump is carried out using COMSOL Multiphysics by coupling fluid structure interaction (fsi) and piezoelectric (pzd) physics module. The transient response of the flow rate and pressure distribution was studied. The dependency of flow rate with applied voltage, frequency and aspect ratio of the diffuser/nozzle was characterised by various size of the piezo layer and diaphragm layer. The effect on flow rate with polymethylmethacrylate and polydimethylsiloxane with single layer and stacked double layer was characterised. Sinusoidal actuating voltage is applied on piezoelectric material and varied up to a maximum of 180 V, 100 Hz. The simulation result proved that the flow rate can be effectively controlled with the application of appropriate combination of external sinusoid voltage, frequency and aspect ratio of the diffuser/nozzle.